Aiding students, buying students financial aid in America - Wilkinson, Rupert (Vanderbilt Univ. Press, 2005)
Wilkinson traces the history of undergraduate financial aid at American colleges and universities; the origins, purposes, and impacts of merit- and need-based aid; the federal government's role; the evolution of elite private institutions; and the current climate and concerns. The concluding chapter lays out how these factors, combined with increasing costs of attending college, impact low-income minority students and how reforms on campuses and in Washington, DC, can better serve higher education and the more disadvantaged students.